2017
DOI: 10.1186/s12875-017-0596-2
|View full text |Cite|
|
Sign up to set email alerts
|

The 5As team patient study: patient perspectives on the role of primary care in obesity management

Abstract: BackgroundOver 60% of people have overweight or obesity, but only a third report receiving counselling from primary care providers. We explored patients’ perspectives on the role of primary care in obesity management and their experience with existing resources, with a view to develop an improved understanding of this perspective, and more effective management strategies.MethodsQualitative study employing semi-structured interviews and thematic analysis, with a sample of 28 patients from a cohort of 255 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 34 publications
5
63
1
7
Order By: Relevance
“…As such, it is essential to explore the impact of adverse experiences prior to the onset of weight gain on eating habits, physical activity, social life, and emotional reactions. Furthermore, listening to patients’ experiences and tailoring the best possible intervention programs has also been recommended as best practice [9, 26]. The results of our study nevertheless underscore the importance of psychological evaluation in the presurgical assessments of patients with morbid obesity and indicate that adverse life experiences might play a role in the patients’ treatment choice for obesity.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…As such, it is essential to explore the impact of adverse experiences prior to the onset of weight gain on eating habits, physical activity, social life, and emotional reactions. Furthermore, listening to patients’ experiences and tailoring the best possible intervention programs has also been recommended as best practice [9, 26]. The results of our study nevertheless underscore the importance of psychological evaluation in the presurgical assessments of patients with morbid obesity and indicate that adverse life experiences might play a role in the patients’ treatment choice for obesity.…”
Section: Discussionmentioning
confidence: 58%
“…Nevertheless, BMI and DM2 remain the predominant predictors of bariatric surgery as obesity treatment [8]. The importance of building healthy therapeutic relations between patients and healthcare providers was demonstrated in a recent study that assessed patient perspectives in the role of primary care in obesity management [9]. Also, another recently published study revealed divergence in perception and attitudes between patients with obesity and HCP’s perspective of obesity treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…Employers in the ACTION Study Canada and United States reported greater efficacy of their companies' wellness programs than did PwO; however, the wellness programs were not necessarily specific to obesity management. Understanding the attitudes of Canadian HCPs, PwO and employers towards obesity management is critical for overcoming barriers that prevent PwO from seeking and receiving support and medical treatment; fostering a workplace culture that recognizes and treats obesity as a chronic disease; and generating strategies and new delivery systems to improve collaborative, evidence‐based and patient‐centred care …”
Section: Discussionmentioning
confidence: 99%
“…Over past decades, the scientific understanding of obesity and its associated complications has led to obesity being increasingly recognized as a chronic disease requiring long‐term management . However, barriers exist to the optimal management of obesity in healthcare systems, including deep‐rooted weight bias, common misperceptions about the complexity and chronic, relapsing nature of obesity, lack of training among healthcare providers (HCPs) and the use of non‐evidence‐based recommendations . Given the significant and growing impact of obesity on Canadians, it is important to understand perceptions and behaviours, both of people with obesity (PwO) and HCPs, in order to optimize management of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of enablers, having ongoing support from health professionals and being able to attend community programs were seen as important enablers. While patients’ lack of motivation was a barrier highlighted in the present study and in other studies, research evaluating patients’ perspectives on weight management revealed that accountability to health professionals was perceived by patients as a way of maintaining their motivation …”
Section: Discussionmentioning
confidence: 58%